Preparation method of soft magnetic composite material and stator sheet for micro motor

CN114360832BActive Publication Date: 2026-10-27SHANDONG JINGCHUANG MAGNETOELECTRIC IND TECH RES INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202011098908.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-10-14
Publication Date
2026-10-27
Estimated Expiration
2040-10-14

AI Technical Summary

Technical Problem

要制备出饱和磁感应强度及磁导率高、损耗尤其是低频下磁滞损耗低的电机定子用SMC材料,就目前专利所公布的工艺没有明确概述,无法进行满足该性能的材料制备

Benefits of technology

[0026]本发明从铁粉原材料到绝缘包覆电介质层,然后进行导电层的包覆,形成新型的软磁复合材料;用制备的软磁复合材料电化学沉积在50μm厚的铜箔环上制成为定子片,制备出饱和磁感应强度及磁导率高、损耗低的异质复合定子片,用于电机转速达12万转微电机定子。可将微电机的可靠性提高2-4倍,且具有高频(转速每分钟超过12万转)的显著优势-低损耗;复合材料高的磁感应强度(2T)保证其具有更高的功率(约2倍),本发明成功制备具有电介质层(绝缘层)、表面导电层的高频微电机用软磁复合材料用异质定子。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114360832B_ABST
    Figure CN114360832B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of soft magnetic composite material and the preparation method of stator sheet for micro motor, belong to micro motor preparation technical field.The above-mentioned soft magnetic composite material is composed of soft magnetic powder, dielectric layer and conductive layer, the outer surface of the soft magnetic powder is coated with the dielectric layer, the outer surface of the dielectric layer is coated with the conductive layer.The present application prepares the heterogeneous composite stator sheet with high saturation magnetic induction intensity and permeability, low loss, for motor speed reaches 12 million revolutions micro motor stator.Improve the reliability of micro motor, with the significant advantage of high frequency (speed per minute more than 12 million revolutions)-low loss;The high magnetic induction intensity (2T) of soft magnetic composite material ensures that it has higher power (about 2 times).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of micro-motor fabrication technology, specifically providing a method for preparing a soft magnetic composite material and a stator plate for a micro-motor. Background Technology

[0002] Iron-based soft magnetic composite materials (also known as magnetic powder cores) possess the characteristics of high magnetic induction intensity, high magnetic permeability, low coercivity, and low loss, making them promising candidates for applications in electrical, computer, and communication fields. With global energy scarcity, reducing energy consumption has become an urgent requirement; therefore, the low loss of soft magnetic composite materials offers significant advantages for replacing current applications such as motor stators.

[0003] Magnetic powder cores come in many varieties, the most common being iron powder cores, iron-nickel magnetic powder cores, iron-silicon-aluminum magnetic powder cores, iron-nickel-molybdenum magnetic powder cores, and iron-silicon-nickel magnetic powder cores. Iron powder cores were the first to be studied. Their advantages lie in their good formability, high saturation magnetic induction, and high effective permeability, along with their low cost, making them very suitable for industrial production applications. However, iron powder cores have low resistivity, resulting in excessive eddy current losses, high magnetic losses, and poor high-frequency performance when operating under an alternating current field.

[0004] Effective insulation coating is key to addressing the high eddy current loss in iron powder cores. Common coating methods are divided into organic and inorganic coatings. Numerous patents exist for related processes; for example, CN103666364A uses coupling agents and organic resins for coating; CN104368807A uses sol-gel to coat iron powder with nano-alumina, followed by coating with coupling agents and silicone resin—an inorganic-organic composite coating; and CN104036899A mentions forming an Fe4N coating layer on the iron powder surface through a nitriding process.

[0005] Patent CN104157389A discloses a method for preparing high-performance soft magnetic composite materials, including steps such as selecting and proportioning iron powder, insulating coating, pressing, high-temperature annealing, ternary grinding, impregnation, and baking. The use of high-purity water-atomized iron powder and carbonyl iron powder effectively avoids spikes or double peaks, while maintaining a good normal distribution, effectively improving the pressing density of the iron core component. The use of nano-silicon nitride and aluminum nitride dielectric materials to coat the iron powder effectively prevents oxidation and helps reduce eddy current losses. This invention features a simple, efficient, and complete coating process. The insulating coating layer on the iron powder surface effectively reduces the magnetic loss of the iron core component. The resulting component has low eddy current losses, high saturation magnetic induction, and high permeability and resistivity, exhibiting superior magnetic and mechanical properties. This processing method is low-cost and has high forming accuracy.

[0006] Existing patents outline different methods for preparing SMC materials, but they lack detailed explanations of processes such as raw material selection, coating agent selection, and coating method selection. The impact of each step on the final material performance is not elucidated. With the successful application of SMC materials in high-efficiency motor stators, the demand for SMC materials in this field is gradually increasing. However, the processes disclosed in current patents do not provide a clear overview of how to prepare SMC materials for motor stators that possess high saturation magnetic induction and permeability, as well as low losses, especially low-frequency hysteresis losses, to meet these performance requirements, making it impossible to prepare materials that satisfy these performance criteria. Summary of the Invention

[0007] To address the problems existing in the prior art, this invention provides a method for preparing soft magnetic composite materials and stator laminations for micromotors. This invention produces a heterogeneous composite stator with high saturation magnetic induction intensity and permeability, and low loss, suitable for use in micromotors with motor speeds up to 120,000 rpm. This improves the reliability of the micromotor by 2-4 times and offers significant advantages such as high frequency (speeds exceeding 120,000 rpm) and low loss; the high magnetic induction intensity (2T) of the soft magnetic composite material ensures higher power (approximately twice the power).

[0008] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0009] On one hand, the present invention provides a soft magnetic composite material, which is composed of soft magnetic powder, a dielectric layer and a conductive layer, wherein the soft magnetic powder is coated with the dielectric layer and the dielectric layer is coated with the conductive layer.

[0010] Furthermore, the dielectric layer has a thickness of 5-15 nm; the conductive layer has a thickness of 15-50 nm.

[0011] The dielectric layer is a phosphate coating layer or a tetraethyl orthosilicate coating layer; the conductive layer is a nickel oxide and cobalt tetroxide coating layer.

[0012] Furthermore, the soft magnetic powder is a secondary reduced iron powder with a particle size of 10-30 μm and a purity of >99%.

[0013] On the other hand, the present invention provides a method for preparing the above-mentioned soft magnetic composite material, comprising:

[0014] Step 1: Take the soft magnetic powder and sieve it to remove the coarse particles. Set aside the sieved powder.

[0015] Step 2: Coat the above soft magnetic powder with a dielectric layer to form an insulating coating material;

[0016] Step 3: Coat the insulating material from Step 2 with a conductive layer to obtain the soft magnetic composite material.

[0017] Furthermore, step 1 specifically involves selecting 10-30μm secondary reduced iron powder with a purity >99%, sieving it to remove coarse particles, and using the sieved powder for later use.

[0018] Further, step 2 specifically involves: mixing soft magnetic powder with alcohol at a ratio of 1g:1ml, adding 60ml of a 0.1-0.4wt% dielectric alcohol solution per kilogram, stirring for a period of time, drying, and sieving to form a uniform 5-15nm dielectric layer.

[0019] Furthermore, step 3 specifically includes:

[0020] The insulating coating material is mixed with acetone at a ratio of 1g:1ml for soft magnetic powder, and 0.2-0.5% by weight of nickel oxide is added. The mixture is then ball-milled for coating. Then, 0.2-0.5% by weight of cobalt tetroxide is added and ball-milled for coating. The mixture is then dried, sieved, and a conductive layer of 15-50nm is formed.

[0021] During the ball milling process, the material-to-ball ratio is 2:1, the ball milling speed is 50 rpm, and the ball milling time is 30 minutes.

[0022] In another aspect, the present invention also provides a method for preparing stator plates for micro motors, which is prepared by electrochemically depositing the above-mentioned soft magnetic composite material on a 50μm thick copper foil ring substrate.

[0023] Furthermore, the electrolyte for electrochemical deposition is a mixture of CoSO4·7H2O 280 g / L, COCl·6H2O 10 g / L, NaH2PO2·H2O 20 g / L and H2BO3 30 g / L; the substrate serves as the cathode and the anode is a platinum electrode.

[0024] The present invention also provides a microelectrode, comprising a stator plate for a microelectrode obtained by the above method.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] This invention produces a novel soft magnetic composite material by first preparing iron powder as raw material, then coating it with an insulating dielectric layer, followed by a conductive layer. The prepared soft magnetic composite material is electrochemically deposited onto a 50μm thick copper foil ring to create a stator plate. This process produces a heterogeneous composite stator plate with high saturation magnetic induction intensity and permeability, and low loss, suitable for use in micromotor stators with speeds up to 120,000 rpm. This can improve the reliability of micromotors by 2-4 times and offers significant advantages such as high frequency (speeds exceeding 120,000 rpm) and low loss. The high magnetic induction intensity (2T) of the composite material ensures higher power (approximately twice the power). This invention successfully prepares a heterogeneous stator for high-frequency micromotors using soft magnetic composite materials with a dielectric layer (insulating layer) and a surface conductive layer. Attached Figure Description

[0027] Figure 1 This is a structural diagram of the soft magnetic composite material in Embodiment 1 of the present invention;

[0028] Figure 2 This is a schematic diagram of electrochemical deposition in Example 7 of the present invention;

[0029] Figure 3 This is a schematic diagram of the stator sheet obtained by electrochemical deposition using the soft magnetic composite material prepared in Example 4 in Example 7 of the present invention. Detailed Implementation

[0030] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0031] Unless otherwise specified, all reagents and materials used in the examples and comparative examples are commercially available.

[0032] This invention provides a method for preparing soft magnetic composite materials and stator laminations for micro motors, and specific embodiments are as follows.

[0033] Example 1

[0034] A soft magnetic composite material, such as Figure 1 As shown, it is composed of soft magnetic powder, a dielectric layer and a conductive layer. The soft magnetic powder is coated with a dielectric layer, and the dielectric layer is coated with a conductive layer.

[0035] Preferably, the dielectric layer has a thickness of 5-15 nm; the conductive layer has a thickness of 15-50 nm.

[0036] Preferably, the dielectric layer is a phosphate coating layer or a tetraethyl orthosilicate coating layer; the conductive layer is a nickel oxide and cobalt tetroxide coating layer. The soft magnetic powder is secondary reduced iron powder with a particle size of 10-30 μm and a purity >99%.

[0037] The preparation method of the above-mentioned soft magnetic composite material includes:

[0038] Step 1: Select secondary reduced iron powder with a size of 10-30μm and a purity of >99%, pass it through a 460-mesh sieve to remove coarse particles, and use the sieved powder.

[0039] Step 2: Dissolve 1000g of iron powder in 1000ml of alcohol, add 60ml of 0.1wt% phosphate alcohol solution per kilogram, stir for 30 minutes, dry at 50℃, pass through a 40-mesh sieve to form a uniform dielectric layer (insulating layer), and obtain the insulating coating material.

[0040] Step 3: Dissolve the insulating coating material in acetone. Add 0.2% nickel oxide (by weight of iron powder) to 1000g of secondary reduced iron powder in 1000ml of acetone. Ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Then add 0.2% cobalt tetroxide (by weight of iron powder) and ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Finally, dry the mixture and pass it through a 40-mesh sieve to form a conductive layer.

[0041] Example 2

[0042] A method for preparing a soft magnetic composite material, comprising:

[0043] Step 1: Same as Example 1;

[0044] Step 2: Weigh 1000g of iron powder, dissolve 1000g of iron powder in 1000ml of alcohol, add 60ml of 0.4wt% phosphate alcohol solution per kilogram, stir for 30 minutes, dry at 50℃, pass through a 40-mesh sieve to form a uniform dielectric layer (insulating layer), and obtain the insulating coating material.

[0045] Step 3: Dissolve the insulating coating material in acetone. Add 0.5% nickel oxide (by weight of iron powder) to 1000g of secondary reduced iron powder in 1000ml of acetone. Ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Then add 0.2% cobalt tetroxide (by weight of iron powder) and ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Finally, dry the mixture and pass it through a 40-mesh sieve to form a conductive layer.

[0046] Example 3

[0047] A method for preparing a soft magnetic composite material, comprising:

[0048] Step 1: Same as Example 1;

[0049] Step 2: Weigh 1000g of iron powder, dissolve 1000g of iron powder in 1000ml of alcohol, add 60ml of 0.3wt% phosphate alcohol solution per kilogram, stir for 30 minutes, dry at 50℃, pass through a 40-mesh sieve to form a uniform dielectric layer (insulating layer), and obtain the insulating coating material.

[0050] Step 3: Dissolve the insulating coating material in acetone. Add 0.3% nickel oxide (by weight of iron powder) to 1000g of secondary reduced iron powder in 1000ml of acetone. Ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Then add 0.5% cobalt tetroxide (by weight of iron powder) and ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Finally, dry the mixture and pass it through a 40-mesh sieve to form a conductive layer.

[0051] Example 4

[0052] A method for preparing a soft magnetic composite material, comprising:

[0053] Step 1: Same as Example 1;

[0054] Step 2: Weigh 1000g of iron powder, dissolve 1000g of iron powder in 1000ml of alcohol, add 60ml of 0.1wt% phosphate alcohol solution per kilogram, stir for 30 minutes, dry at 50℃, pass through a 40-mesh sieve to form a uniform dielectric layer (insulating layer), and obtain the insulating coating material.

[0055] Step 3: Dissolve the insulating coating material in acetone. Add 0.1% nickel oxide (by weight of iron powder) to 1000g of secondary reduced iron powder in 1000ml of acetone. Ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Then add 0.3% cobalt tetroxide (by weight of iron powder) and ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Finally, dry the mixture and pass it through a 40-mesh sieve to form a conductive layer.

[0056] Example 5

[0057] A method for preparing a soft magnetic composite material, comprising:

[0058] Step 1: Same as Example 1;

[0059] Step 2: Weigh 1000g of iron powder, dissolve 1000g of iron powder in 1000ml of alcohol, add 60ml of 0.2wt% phosphate alcohol solution per kilogram, stir and dry, pass through a 40-mesh sieve to form a uniform dielectric layer (insulating layer), and obtain the insulating coating material.

[0060] Step 3: Dissolve the insulating coating material in acetone. Add 0.2% nickel oxide (by weight of iron powder) to 1000g of secondary reduced iron powder in 1000ml of acetone. Ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Then add 0.2% cobalt tetroxide (by weight of iron powder) and ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Finally, dry the mixture and pass it through a 40-mesh sieve to form a conductive layer.

[0061] Example 6

[0062] A method for preparing a soft magnetic composite material, comprising:

[0063] Step 1: Same as Example 1;

[0064] Step 2: Weigh 1000g of iron powder, dissolve 1000g of iron powder in 1000ml of alcohol, add 60ml of 0.1wt% tetraethyl orthosilicate alcohol solution per kilogram, stir and dry, pass through a 40-mesh sieve to form a uniform dielectric layer (insulating layer), and obtain the insulating coating material.

[0065] Step 3: Dissolve the insulating coating material in acetone. Add 0.2% nickel oxide (by weight of iron powder) to 1000g of secondary reduced iron powder in 1000ml of acetone. Ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Then add 0.3% cobalt tetroxide (by weight of iron powder) and ball mill the mixture for coating, with a material-to-ball ratio of 2:1, a ball milling speed of 50 rpm, and a ball milling time of 30 minutes. Finally, dry the mixture and pass it through a 40-mesh sieve to form a conductive layer.

[0066] To further highlight the beneficial effects of the present invention, due to space limitations, only Example 4 is used as an example to construct the following comparative example.

[0067] Comparative Example 1

[0068] In step 2 of this comparative example, the dielectric layer is epoxy resin, and the other conditions are the same as in Example 4.

[0069] Comparative Example 2

[0070] In step 2 of this comparative example, the dielectric layer is phenolic resin, and the other conditions are the same as in Example 4.

[0071] Comparative Example 3

[0072] In step 2 of this comparative example, the dielectric layer is silicone resin, and the other conditions are the same as in Example 4.

[0073] Comparative Example 4

[0074] In step 3 of this comparative example, cobalt tetroxide is omitted, and the remaining conditions are the same as in Example 4.

[0075] Comparative Example 5

[0076] In step 3 of this comparative example, nickel oxide is omitted, and the remaining conditions are the same as in Example 4.

[0077] Comparative Example 6

[0078] In this comparative example, cobalt tetroxide in step 3 is replaced with tungsten trioxide, and the other conditions are the same as in Example 4.

[0079] Comparative Example 7

[0080] In this comparative example, nickel oxide in step 3 was replaced with tungsten trioxide, and the remaining conditions were the same as in Example 4.

[0081] Comparative Example 8

[0082] In this comparative example, cobalt tetroxide in step 3 is replaced with niobium pentoxide, and the other conditions are the same as in Example 4.

[0083] Comparative Example 9

[0084] In this comparative example, nickel oxide in step 3 was replaced with niobium pentoxide, and the remaining conditions were the same as in Example 4.

[0085] Comparative Example 10

[0086] In this comparative example, nickel oxide in step 3 was replaced with niobium pentoxide, and cobalt tetroxide was replaced with tungsten trioxide. The remaining conditions were the same as in Example 4.

[0087] Example 7

[0088] A method for preparing a stator lamination for a micromotor using soft magnetic composite materials is disclosed. The method involves electrochemically depositing the soft magnetic composite materials prepared in Examples 1-6 and Comparative Examples 1-10 onto a 50 μm thick copper foil ring substrate. The electrochemical deposition process is described below. Figure 2 Stator wafers before and after electrochemical deposition Figure 3 As shown. Specifically:

[0089] Step 1: Place the substrate in solution 1 and stir at 55°C for 30 minutes to remove impurities from the substrate surface; rinse the substrate with flowing distilled water for 5 seconds; then air dry for 30 seconds.

[0090] Step 2: Place the substrate in Solution 2 at room temperature for 30 seconds to activate the surface; rinse the substrate with running distilled water for 5 seconds; air dry for 30 seconds;

[0091] Step 3: Electrochemically deposit a Co-P structure from the electrolyte using a DC power supply and an electrochemical cell. The substrate serves as the cathode of the electrochemical cell; it is connected to the - terminal of the DC power supply; the platinum current collector serves as the anode, connected to the + terminal of the DC power supply; the current density is 25 mA / cm². 2 Temperature 25℃, time 25 minutes; then rinse the substrate with running distilled water for 5 seconds;

[0092] Solution 1 is a mixed solution of NaOH 30g / l, Na2CO3 30g / l, Na3PO4·12H2O 30g / l and synthetic alcohol ALM1 0.4g / l, and solution 2 is H2SO4 50g / l.

[0093] The electrolyte for electrochemical deposition is a mixture of 280 g / L CoSO4·7H2O, 10 g / L CoCl·6H2O, 20 g / L NaH2PO2·H2O, and 30 g / L H2BO3; the substrate serves as the cathode, and the anode is a platinum electrode.

[0094] The performance of the stator plates obtained by using the soft magnetic composite materials prepared in Examples 1-6 and Comparative Examples 1-10 was tested according to the standard GB 13012-2008-T "Measurement Method of DC Magnetic Properties of Soft Magnetic Materials", and the results are shown in Table 1.

[0095] Table 1

[0096]

[0097]

[0098] As shown in Table 1, the stator laminations prepared from the soft magnetic composite material of this invention have high permeability and saturation magnetic induction, and low remanent magnetic induction and coercivity, ensuring that the micromotors prepared from these stator laminations have high power. When the prepared stator laminations are used in the stator of a micromotor with a motor speed of up to 120,000 rpm, they exhibit extremely low losses, while the high magnetic induction (2T) ensures even higher power.

[0099] Compared with conventional organic insulating coatings (Comparative Examples 1-3), the stator sheets obtained by phosphoric acid coating and tetraethyl orthosilicate coating in this invention have higher saturation magnetic induction intensity.

[0100] The two conductive layer material combinations selected in this invention significantly improve the magnetic properties of the stator segments compared to other materials (Comparative Examples 4-10).

[0101] In summary, the stator plates prepared by the soft magnetic composite material of the present invention have the characteristics of high saturation magnetic induction intensity and high magnetic permeability. When used in high-frequency micromotors, they can improve the reliability of micromotors by 2-4 times and have the significant advantages of high frequency (speed exceeding 120,000 revolutions per minute) and low loss. At the same time, the high magnetic induction intensity (2T) of the soft magnetic composite material ensures that it has higher power (about 2 times).

[0102] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A soft magnetic composite material, characterized in that, It is composed of soft magnetic powder, a dielectric layer and a conductive layer, wherein the soft magnetic powder is coated with the dielectric layer, and the dielectric layer is coated with the conductive layer. The dielectric layer has a thickness of 5-15 nm; the conductive layer has a thickness of 15-50 nm. The dielectric layer is a phosphate coating layer or an orthosilicate coating layer; the dielectric layer is prepared by the following method: soft magnetic powder and alcohol are mixed at a ratio of 1g:1ml, 60ml of dielectric alcohol solution with a concentration of 0.1-0.4wt% is added per kilogram, the mixture is stirred for a period of time, dried, and sieved to form a uniform dielectric layer of 5-15nm. The conductive layer is a nickel oxide and cobalt tetroxide coating layer; the conductive layer is prepared by the following method: the prepared insulating coating material is mixed with acetone at a ratio of 1g:1ml for soft magnetic powder, 0.2-0.5% by weight of nickel oxide of soft magnetic powder is added, and ball milling is performed for coating; then 0.2-0.5% by weight of cobalt tetroxide of soft magnetic powder is added, and ball milling is performed for coating; then it is dried, sieved, and a conductive layer of 15-50nm is formed; the ball milling ratio is 2:1, the ball milling speed is 50 rpm, and the ball milling time is 30 minutes; The soft magnetic powder is a secondary reduced iron powder with a particle size of 10-30μm and a purity of >99%.

2. The method for preparing the soft magnetic composite material according to claim 1, characterized in that, include: Step 1: Take the soft magnetic powder and sieve it to remove the coarse particles. Set aside the sieved powder. Step 2: Coat the above soft magnetic powder with a dielectric layer to form an insulating coating material; Step 3: Mix the insulating coating material from Step 2 with nickel oxide and ball mill for coating. Then add cobalt tetroxide and ball mill for coating to obtain the soft magnetic composite material.

3. The method for preparing the soft magnetic composite material according to claim 2, characterized in that, Step 1 specifically involves selecting 10-30μm secondary reduced iron powder with a purity >99%, sieving it to remove coarse particles, and using the sieved powder for later use.

4. The method for preparing the soft magnetic composite material according to claim 2, characterized in that, Step 2 specifically involves mixing soft magnetic powder with alcohol at a ratio of 1g:1ml, adding 60ml of a 0.1-0.4wt% dielectric alcohol solution per kilogram, stirring for a period of time, drying, and sieving to form a uniform 5-15nm dielectric layer.

5. The method for preparing the soft magnetic composite material according to claim 2, characterized in that, Step 3 specifically involves: mixing the prepared insulating coating material with acetone at a ratio of 1g:1ml for soft magnetic powder, adding 0.2-0.5% by weight of nickel oxide from the soft magnetic powder, and ball milling for coating; then adding 0.2-0.5% by weight of cobalt tetroxide from the soft magnetic powder, and ball milling for coating; then drying, sieving, and forming a conductive layer of 15-50nm. The ball mill has a material-to-ball ratio of 2:1, a milling speed of 50 rpm, and a milling time of 30 minutes.

6. A method for preparing stator laminations for micro motors, characterized in that, The soft magnetic composite material obtained by any one of the preparation methods described in claims 2-5 is prepared by electrochemical deposition on a substrate.

7. The method for preparing stator laminations for micromotors according to claim 6, characterized in that, The electrolyte for electrochemical deposition is a mixture of CoSO4·7H2O 280 g / L, CoCl·6H2O 10 g / L, NaH2PO2·H2O 20 g / L and H2BO3 30 g / L; the substrate serves as the cathode and the anode is a platinum electrode.

8. A micro motor, characterized in that, This includes stator laminations for micromotors prepared by the method described in claim 6 or 7.

Citation Information

Patent Citations

  • Organic insulating binder for metal soft-magnetic composite material and method for preparing metal soft-magnetic composite material

    CN103666364A

  • Preparing method of core-shell structure soft-magnetism composite material

    CN104036899A

  • Preparing method of high-performance soft magnetism composite materials

    CN104157389A

  • Power coating method of metal soft magnetic composite and preparing method of metal soft magnetic composite

    CN104368807A

  • High-conductivity amorphous soft magnetic coating

    CN108620576A